2011
DOI: 10.1016/j.sigpro.2011.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate empirical mode decomposition and application to multichannel filtering

Abstract: empirical mode decomposition and application to multichannel filtering. Signal Processing, Elsevier, 2011, 91 (12) AbstractEmpirical Mode Decomposition (EMD) is an emerging topic in signal processing research, applied in various practical fields due in particular to its data-driven filter bank properties. In this paper, a novel EMD approach called X-EMD (eXtended-EMD) is proposed, which allows for a straightforward decomposition of mono-and multivariate signals without any change in the core of the algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…Nowadays, there are many types of EMD and each one has merits and demerits in processing the signal. For example, eXtended-EMD (X-EMD) [29] can produce better results than MEMD and Turning Tangent EMD (2T-EMD) [30] in dealing with multivariate signal denoising. However, in 2011 Rehman et al also proposed N-A EMD.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are many types of EMD and each one has merits and demerits in processing the signal. For example, eXtended-EMD (X-EMD) [29] can produce better results than MEMD and Turning Tangent EMD (2T-EMD) [30] in dealing with multivariate signal denoising. However, in 2011 Rehman et al also proposed N-A EMD.…”
Section: Discussionmentioning
confidence: 99%
“…Mandic and Goh (2009) described and showed that local optima of multivariate data are not possible to find directly as in univariate EMD. Moreover, the mean envelopes defining an IMF are rather confusing for multivariate signals (Fleureau et al, 2011a(Fleureau et al, , 2011bRehman and Mandic, 2010;Rilling et al, 2007). Consequently, several algorithms have been proposed to overcome this problem, i.e., rotation invariant complex EMD (RIEMD) (Altaf et al, 2007), bivariate EMD (BEMD) (Rilling et al, 2007), and multivariate EMD (MEMD) (Rehman and Mandic, 2010).…”
Section: Multivariate Emd (Memd) and Noise Assisted Memd (Na-memd)mentioning
confidence: 99%
“…These have adverse effects on the performance for fault detection. To alleviate these problems, the variants of EMD, such as EEMD, bivariate empirical mode decomposition (BEMD), and multivariate empirical mode decomposition (MEMD) [22][23][24], have been developed. Moreover, there is a lack of theory to clarify these problems.…”
Section: Introductionmentioning
confidence: 99%